2022
DOI: 10.3390/pathogens11111277
|View full text |Cite
|
Sign up to set email alerts
|

Development, Optimisation and Validation of a Novel Multiplex Real-Time PCR Method for the Simultaneous Detection of Cryptosporidium spp., Giardia duodenalis and Dientamoeba fragilis

Abstract: The enteric protozoan parasites Cryptosporidium spp., Giardia duodenalis and Dientamoeba fragilis are—to various extents—contributors to the burden of gastrointestinal illness in high-income countries. Detection of these pathogens by microscopy examination is challenging because of the limited sensitivity and need for specific staining procedures. We developed and optimised a new multiplex real-time PCR assay for the simultaneous detection of Cryptosporidium spp., G. duodenalis and D. fragilis in clinical (sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The VIASURE D. fragilis assay achieved sensitivity and specificity values of 1 and 0.99 (respectively) in both singleplex and duplex versions. This diagnostic performance was in the higher range of what was previously documented in the use of other commercially available qPCR assays (sensitivity: 0.90-0.96; specificity: 1) [32,33].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The VIASURE D. fragilis assay achieved sensitivity and specificity values of 1 and 0.99 (respectively) in both singleplex and duplex versions. This diagnostic performance was in the higher range of what was previously documented in the use of other commercially available qPCR assays (sensitivity: 0.90-0.96; specificity: 1) [32,33].…”
Section: Discussionsupporting
confidence: 48%
“…Most previous similar studies that evaluated commercial qPCR assays used prospectively collected stool samples that were submitted for routine investigation in clinical settings [21,23,[25][26][27][28][29][30][31][32][33]. In contrast, this survey purposely used a DNA panel with a wide diversity of parasite species and genotypes, with the aim of providing an evidence-based answer to the question of if the evaluated qPCR assays were suitable for the detection of less common or rare species/genotypes and animal-adapted genetic variants with known zoonotic potential and diverse geographical origins.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al observed ~2‐fold to ~240‐fold drop in sensitivity when changing from multiple duplex assays in detecting respiratory viral pathogens to a multiplex platform 30 . Many publications are available to guide the optimisation of multiplex PCR or qPCR 35–37 . However, their primary focus on microbial pathogen detection represents a different context (e.g., microbial pathogen can be cultured to higher titre before extraction), and hence, not all of their considerations are specific to the context of doping control.…”
Section: Resultsmentioning
confidence: 99%
“…Parker et al observed $2-fold to $240-fold drop in sensitivity when changing from multiple duplex assays in detecting respiratory viral pathogens to a multiplex platform 30. Many publications are available to guide the optimisation of multiplex PCR or qPCR [35][36][37]. F I G U R E 1 The qPCR efficiency of each transgene in the multiplex qPCR assay.…”
mentioning
confidence: 99%